2007
DOI: 10.1007/s00040-007-0911-3
|View full text |Cite
|
Sign up to set email alerts
|

Nestmate recognition in a neotropical polygynous wasp

Abstract: In social insects, nestmate recognition systems can be dynamic and modulated in response to various kinds of genetic and environmental cues. For example, multiple-queen colonies can possess weak recognition abilities relative to single-queen colonies, due to broader exposure to heritable and environmentally derived nestmate recognition cues. We conducted field experiments to examine nestmate recognition ability in a neotropical polygynous wasp, Polybia paulista. Despite the fact that the effective queen number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
(47 reference statements)
0
14
1
Order By: Relevance
“…In addition, Kudô 2007 suggests that in colonies of P. paulista the newly emerged workers acquire chemical signatures specific to their colonies within a couple of days after emergence and, in experiments of transfer of individuals between colonies, the acceptance rate of young wasps depends on the stage of the receiver colony (Kudô et al 2010). In the same species, workers are able to distinguish larvae from their own colony from intruders, suggesting that even larvae recognition by workers might be mediated by specific colonial signals (Kudô et al, 2017).…”
Section: Chmentioning
confidence: 99%
“…In addition, Kudô 2007 suggests that in colonies of P. paulista the newly emerged workers acquire chemical signatures specific to their colonies within a couple of days after emergence and, in experiments of transfer of individuals between colonies, the acceptance rate of young wasps depends on the stage of the receiver colony (Kudô et al 2010). In the same species, workers are able to distinguish larvae from their own colony from intruders, suggesting that even larvae recognition by workers might be mediated by specific colonial signals (Kudô et al, 2017).…”
Section: Chmentioning
confidence: 99%
“…Results clearly showed that monoandry is the rule for the four Japanese bumble bee species. Reconstructing patrilines is also helpful to understand interactions within and between partrilines in polygynous social insects (Kudô et al, 2007).…”
Section: Application Of Slca In the Fieldmentioning
confidence: 99%
“…Discrimination between nestmates and non-nestmates, which are usually kin and non-kin, respectively, is often represented as a higher tolerance towards nestmates than to non-nestmates, and is widely observed among social wasps 8,9,19 . Cuticular hydrocarbons have been thought to be responsible for nestmate recognition because some social wasps are known to have colony-specific hydrocarbon profiles, for example, Dolichovespula maculate 2 , Vespula squamosa, V. macurifrons 1 , Vespa crabro 1,3,16 , Polistes fuscatus 7 , Polistes exclamans 18 , Polistes biglumis bimaculatus: 11,12 , Polistes dominulus 4 , and Polistes satan 21 .…”
Section: Introductionmentioning
confidence: 99%